Analysis of Factors Affecting Economic Achievements of High School Students SMA Negeri Kecamatan Koto Tangah Kota Padang Sumatera Barat - Stevani, Stevani; Gumanti, Dessyta (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
This study aims to find the factors that affect the economic achievement of high school students SMA Negeri Koto Tangah Subdistrict Padang. The population in this study were all students of SMA Negeri in Koto Tangah Subdistrict namely SMAN 7 Kota Padang, SMAN 8 Kota Padang and SMAN 13 Kota Padang, sample determination using proportional random sampling method with 257 respondents. Analyzer used is Factor Analysis and Multiple Regression. The result of the research shows that there are three factors that influence student achievement such as (a) Teaching Instrument factor, (b) Personal ability factor, (c) Social Support factor. Of the three factors that affect student achievement of SMA Negeri Kecamatan Koto Tangah Padang , the dominant factor that has a big influence is the Teaching Instrument factor. The result of multiple regression analysis showed that from three factors have a significant effect on student achievement that is with the acquisition of sig <0,05. It can be concluded that the creativity of teachers, the understanding of teacher materials, the completeness of the means of learning infrastructure, learning references and school atmosphere are the factors that most influence the economic achievement of students of SMA Negeri Koto Tangah Subdistrict, Padang West Sumatra.